Characterization, feasibility and optimization of Agaricus subrufescens growth based on chemical elements on casing layer - Cunha Zied, D. [UNESP]; Pardo-Gimenez, A.; de Almeida Minhoni, M. T. [UNESP]; Villas Boas, Roberto Lyra [UNESP]; Alvarez-Orti, M.; Pardo-Gonzalez, J. E. (Elsevier B.V., 2012)
The aim of this study was to analyze yields, biological efficiency, earliness (expressed as days to first harvest), and precociousness and establish models for the mushroom growing according to these parameters. The experiment followed a double factorial design with four sources of calcium (calcitic limestone, calcitic limestone + gypsum, dolomitic limestone and dolomitic limestone + gypsum) and 2 application times (25 days before casing and at the moment of casing), with 4 replicates for each treatment. Different calcium sources influenced differently Agaricus subrufescens production, especially as regards earliness, which showed significantly higher values when dolomitic limestone with gypsum was applied. Yield and biological efficiency were negatively correlated with H + AL, organic matter and Mg amount. Furthermore, earliness was positively correlated with H + Al, organic matter, and the amount of Mg and Fe. Finally, negative correlations were observed between precociousness and the amount of Ca, SB (sum of base), CEC (cation exchange capacity) and V% (percentage of base saturation). The models presented in this work are extremely important for predicting the agronomic performance of Agaricus subrufescens on the basis of chemical analysis provided by the casing soil. (c) 2012 King Saud University. Production and hosting by Elsevier B. V. All rights reserved.
Keywords: Almond Mushroom; Growth models; Personal correlation; Calcium sources; Mushroom cultivation